2022
DOI: 10.1002/cne.25304
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐hierarchical plasticity of corticofugal projections to dLGN after neonatal monocular enucleation

Abstract: Perception is the result of interactions between the sensory periphery, thalamus, and cerebral cortex. Inputs from the retina project to the first‐order dorsal lateral geniculate nucleus (dLGN), which projects to the primary visual cortex (V1). In return, the cortex innervates the thalamus. While layer 6 projections innervate all thalamic nuclei, cortical layer 5 neurons selectively project to the higher order lateral posterior nucleus (LP) and not to dLGN. It has been demonstrated that a subpopulation of laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 79 publications
0
16
2
Order By: Relevance
“…Scale in c = 50 µm and also applies to d with and without retinofugal input. While previous reports have suggested that layer V cortical neurons provide an anomalous source of input following monocular or binocular enucleation (Frangeul et al, 2016;Giasafaki et al, 2022;Grant et al, 2016), we found no differences in the ultrastructure of corticogeniculate terminals in wild-type versus math5 -/mice. We also found no changes in the overall pattern of tectogeniculate or PPT projections in wild-type versus math5 -/mice.…”
Section: Discussioncontrasting
confidence: 96%
See 4 more Smart Citations
“…Scale in c = 50 µm and also applies to d with and without retinofugal input. While previous reports have suggested that layer V cortical neurons provide an anomalous source of input following monocular or binocular enucleation (Frangeul et al, 2016;Giasafaki et al, 2022;Grant et al, 2016), we found no differences in the ultrastructure of corticogeniculate terminals in wild-type versus math5 -/mice. We also found no changes in the overall pattern of tectogeniculate or PPT projections in wild-type versus math5 -/mice.…”
Section: Discussioncontrasting
confidence: 96%
“…These results seem at odds with previous studies using RpB4-cre mice crossed with reporter lines to demonstrate changes in cortical innervation patterns following monocular enucleation (Giasafaki et al, 2022;Grant et al, 2016). Although a subset of tectogeniculate cells contain cre-recombinase in the Rpb4-cre line, we found no apparent expansion of tectogeniculate projections in math5 -/mice.…”
Section: Corticogeniculate Input In the Absence Of Retinogeniculate I...contrasting
confidence: 99%
See 3 more Smart Citations